From Enantioselective to Regiodivergent Epoxide Opening and Radical Arylation – Useful or Just Interesting? - Gansäuer, Andreas (Synlett, 2021)
It is shown how the simple titanocene(III)-catalyzed reductive opening of epoxides has developed from a highly selective desymmetrizing opening of meso-epoxides. The combination of the origins of regioselectivity with atom-economic catalysis in single electron steps results in a highly selective regiodivergent epoxide opening (REO).1 Introduction2 Regiodivergent Epoxide Opening3 Atom Economy and Epoxide Arylation4 REO Arylation5 Words about the Wording6 Conclusion
Keywords: arylation; catalysis; diversity-oriented synthesis; epoxides; regiodivergent; titanocenes